2013
DOI: 10.5761/atcs.oa.12.01943
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Modified Bentall Procedure Using Flanged Composite Aortic Prosthesis

Abstract: Purpose: We have been using the flanged composite aortic prosthesis and Carrel button technique to re-attach the coronary ostia in aortic root replacement procedures at our institution over the last twenty five years. Our objective was to evaluate the long-term results of aortic root replacement with this technique. Methods: A total of 73 patients from January 1984 to August 2010 were included in this study. The median age was 52.7 ± 14.4 years (range 28-80 years). There were 48 male and 25 female patients. 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Nevertheless, Bentall surgery, in particular its modified version, is considered reliable and relatively safe. Therefore, long-term outcomes are rather optimistic [2,17]. In our study, we did not observe substantial differences in HRV parameters of MS patients with FBN1 mutations after surgery compared to those who did not undergo the procedure.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, Bentall surgery, in particular its modified version, is considered reliable and relatively safe. Therefore, long-term outcomes are rather optimistic [2,17]. In our study, we did not observe substantial differences in HRV parameters of MS patients with FBN1 mutations after surgery compared to those who did not undergo the procedure.…”
Section: Discussionmentioning
confidence: 56%
“…The reported mortality rate for elective Bentall surgery ranges from 1 to 5% [17,18] . In addition, Pacini et al [15] reported a 6.9% early-term mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 However, valve graft conduits as described in the original Bentall-DeBono procedure have demonstrated excellent long-term survival and a low rate of aortic reoperation. 1…”
Section: Discussionmentioning
confidence: 99%
“…The use of a mechanical valve graft conduit as described in the original Bentall-DeBono procedure is reliable and safe, with excellent long-term survival and a low rate of aortic reoperation. 1 However, this approach mandates anticoagulation for mechanical valves to prevent thromboembolic complications. Also, for patients receiving bioprosthetic valve graft conduits, it is associated with a certain rate of reoperation due to degeneration of bioprosthetic valves.…”
Section: Introductionmentioning
confidence: 99%